Commentary: Shifting Standards? The ECtHR’s Evolving Approach to Minority Rights - Akbulut, Olgun (Journal on ethnopolitics and minority issues in Europe JEMIE, 2025)
This commentary critically examines the European Court of Human Rights’ (ECtHR) approach to minority rights within the broader human rights framework. The analysis assesses how the Court’s reasoning has reinforced or, recently, deviated from established principles. Through a doctrinal and critical analysis of key judgments, the commentary identifies trends in the Court’s reliance on pluralism, non-discrimination, and democratic participation as guiding principles. While earlier rulings underscored the necessity of protecting cultural, linguistic, and religious identities, recent decisions – particularly regarding Russian-speaking minorities in Latvia – signal a shift, raising concerns on judicial reasoning. The findings highlight inconsistencies in the Court’s application of international minority rights instruments and question the broader implications for legal certainty in minority rights protection.